1999
DOI: 10.1016/s0304-3959(98)00201-2
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling age effects and sex differences in needle pain: ratings of sensory intensity and unpleasantness of venipuncture pain by children and their parents

Abstract: Age and sex differences were investigated in children's self-report of venipuncture pain. Equal numbers of boys and girls aged 3-15 years (n = 110) made separate ratings of the intensity and unpleasantness of their needle pain, using a paired Visual Analogue Scale (VAS) technique. The parents of these children used the same method to give ratings of predicted pain and unpleasantness before the needle, as well as ratings based on observing their child during the needle. Results showed that, across age, children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
5
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(121 citation statements)
references
References 32 publications
10
96
5
2
Order By: Relevance
“…Also consistent with previous studies, correlates of needle fear included younger age and female sex [18,19]. We found that parents under-reported needle fear in their children when compared to children's self-report.…”
Section: Discussionsupporting
confidence: 91%
“…Also consistent with previous studies, correlates of needle fear included younger age and female sex [18,19]. We found that parents under-reported needle fear in their children when compared to children's self-report.…”
Section: Discussionsupporting
confidence: 91%
“…Values obtained in the current study largely exceeded the VAS pain perception scores reported for venipuncture (23,24). The parents in both the venipuncture study and this study rated their children's pain higher than the children did.…”
Section: Discussion Pain Of Injury and Treatmentcontrasting
confidence: 49%
“…In a study comparing needle puncture sensitivity in children aging from 7 to 11 years, and 12 to 16 years, younger ones presented lower thresholds than elder ones (Goodenough et al 1999). In an other study with children undergoing venipuncture and divided in groups that received previous anesthetic block, placebo and no kind of prevention, authors showed age difference with younger children more sensitive, and a strong positive correlation between anxiety and high predictive pain scores (Goodenough et al 1997).…”
Section: Discussionmentioning
confidence: 97%
“…This explanation can justify high anxiety degree influencing pain expectance (Lander & Fowler-Kerry 1991, Capone & Aloisi 2004). It's impossible to register pain report in animals as well as their emotional discomfort; however it's possible to estimate that anxiety by repetition of a same acute and intense stimulus in a period which memory has been poorly fed (GF3) due to short time living produced more vigorous responses with lower pain thresholds, in the same way that the idea that capability to deal with uncomfortable events modifies pain reaction (Lander & Fowler-Kerry 1991, Goodenough et al 1999, Al-Chaer et al 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation